KNOWLEDGE OF FAMILY PREVENTING DIABETIC WOUND IN DIABETES MELITUS PATIENT - Kezia H asuneneng; Johanna Tuegeh; Tati S. Ponidjan (POLTEKKES KEMENKES MANADO, 2018)
Background Diabetes mellitus (DM) is one of the major health problems. in the world. The number of DM cases in North Sulawesi Province in 2016 increased with the number of 4.525 in 2015 to 5.261 patients in 2016, 60% of these patients had diabetic wounds. (Ministry of Health, 2016). The aim of this study was to determine the relationship of knowledge about wound prevention with the incidence of diabetic wounds. Methods This research uses a quantitative approach with a cross-sectional design. The research sample of 50 respondents was a Family of DM patients who seek treatment in the Internal Medicine Room of the Pancaran Kasih GMIM Hospital Manado. Results showed that most respondents lack knowledge with 33 respondents (66%) and were identified with the incidence of diabetic injuries. Test results show the relationship between patient knowledge about DM Wound Prevention with the incidence of DM Wound is p-value = 0,000 (α = 0.05). Conclusion there is a significant relationship between patient knowledge about DM Wound Prevention with the incidence of DM Wound. This findings Suggestions for health workers caring for DM patients, in order to improve education about wound care with a variety of educational methods.